Margaret River - Andrijich, Frances (Fremantle, Western Australia. : Fremantle Press, 2019)
The unique region of Margaret River in Australia's south-west is captured with charm and intimacy through the lens of Frances Andrijich. Frances is one of Australia's finest photographers whose work features in national and international magazines such as Time Magazine, Harper's Bazaar, Gourmet Traveller, Australian Geographic, Vogue and the Weekend Australian Magazine. Margaret River explores the natural beauty and daily life of the place that has become her second home.
Prepublication record (machine generated from publisher information)
Keywords: Wine districts -- Western Australia -- Margaret River Region; Wine and wine making -- Western Australia -- Margaret River Region; Wineries -- Western Australia -- Margaret River Region (Augusta-Margaret River Shire, W.A.); Photography & photographs; Margaret River Region (Augusta-Margaret River Shire, W.A.) -- Description and travel; Margaret River Region (Augusta-Margaret River Shire, W.A.) -- Pictorial works; Augusta (W.A.) -- Description and travel; Augusta (W.A.) -- Pictorial works; Margaret River Region (W.A.) -- Guidebooks; Australian; Photobooks